2004
DOI: 10.1289/ehp.6423
|View full text |Cite
|
Sign up to set email alerts
|

Lead, arsenic, and polycyclic aromatic hydrocarbons in soil and house dust in the communities surrounding the Sydney, Nova Scotia, tar ponds.

Abstract: This study evaluated lead, arsenic, and polycyclic aromatic hydrocarbon (PAH) contamination in the residential communities adjacent to the Sydney, Nova Scotia, tar ponds, the area considered Canada's worst contaminated site. The tar pond remediation policy has been limited to the site and some residential properties. We compared background concentrations in 91 soil samples taken 5-20 km from the coke oven site with those in soil samples from the three communities surrounding the tar ponds: Whitney Pier, Ashby,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 21 publications
1
28
1
Order By: Relevance
“…Entrance floors have only slightly higher loading values than kitchen floors have in St John's, in contrast to results from Sydney, NS, where doorway loadings were found to be an order of magnitude higher than kitchen floor ones (Lambert and Lane 2004). Entrance floor loadings were expected to be higher than those on kitchen floors in St John's because of tracking-in of elevated lead soil on shoes or pets in entranceways and the more frequent cleaning of kitchen surfaces as reported by study participants.…”
Section: Indoor Dust Leadcontrasting
confidence: 84%
See 3 more Smart Citations
“…Entrance floors have only slightly higher loading values than kitchen floors have in St John's, in contrast to results from Sydney, NS, where doorway loadings were found to be an order of magnitude higher than kitchen floor ones (Lambert and Lane 2004). Entrance floor loadings were expected to be higher than those on kitchen floors in St John's because of tracking-in of elevated lead soil on shoes or pets in entranceways and the more frequent cleaning of kitchen surfaces as reported by study participants.…”
Section: Indoor Dust Leadcontrasting
confidence: 84%
“…The relationship between dripline soil lead and indoor dust loadings is the strongest for samples from entrance floors and window sills, which is not unexpected considering their proximity and exposure opportunities (e.g. tracking-in on footwear; Lambert and Lane 2004). In contrast, Rasmussen et al (2001) reported no statistically significant relationship between outdoor soil concentrations and indoor dust concentrations for sampled properties in Ottawa, which they attributed to the much greater influence of indoor leaded paint sources.…”
Section: Relationship Between Soil Lead and Indoor Dust Leadmentioning
confidence: 83%
See 2 more Smart Citations
“…In fact, the simultaneous accumulation of arsenic and polycyclic aromatic hydrocarbons (PAHs) are frequently found and extensively evaluated in several types of anthropogenic industry contaminated sites, such as coking & chemical industry site, mining and metallurgy industry site, lumber and wood production site, etc, even the urban residual areas (Lambert and Lane, 2004;Elgh-Dalgren et al, 2009;Kay et al, 2008). However, up to date, methods for remediation of arsenic and PAHs cocontamination are scarce to report.…”
Section: Introductionmentioning
confidence: 99%